2016
DOI: 10.1016/j.annepidem.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of family, dentition, and dental caries on the salivary microbiome

Abstract: Background Family members share genes, environment and microbial communities. If there is a strong effect of family on the salivary microbiota, controlling for family will enhance identification of microbial communities associated with cariogenesis. The current study was designed to assess the similarity of the salivary microbiome among families and the association between the salivary microbiome and dental decay taking age into account. Methods We selected families (n= 49) participating in the cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
2
14
1
2
Order By: Relevance
“…Furthermore, few studies included young adults as subjects. A cross-sectional study exploring salivary microbiomes among families, including young adults, reported that dental caries did not impact microbial diversity [28]. While our findings support the results of this study, further cohort studies are required to investigate the relationship between microbiome diversity and an increase in dental caries.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, few studies included young adults as subjects. A cross-sectional study exploring salivary microbiomes among families, including young adults, reported that dental caries did not impact microbial diversity [28]. While our findings support the results of this study, further cohort studies are required to investigate the relationship between microbiome diversity and an increase in dental caries.…”
Section: Discussionsupporting
confidence: 78%
“…While the diversity did not dramatically change from 1 week to 8 weeks and again to 1 year, there were significant compositional changes which signify the role of factors, such as diet, dentition, salivary flow rate, oral health, siblings etc., have to play. We did however observe a lower diversity at all ages in the infant oral microbiota compared to the maternal 'adult' salivary microbiota, with similar compositional differences which have been identified previously in the salivary microbiome between adult and infant [64][65][66]. The diversity gap between the mother and infant oral microbiota increased as the infant grew in age demonstrating closer relatedness at a younger age.…”
Section: Discussionsupporting
confidence: 84%
“…For example, although the volunteers were all healthy at the time of saliva collection, it is possible that undetected differences in oral health might be influencing bacterial diversity. However, a recent study found a negligible impact of dental caries on the salivary microbiome [ 43 ]. Focusing on only a portion of the 16S rRNA gene (in order to utilize the NGS capacity) instead of analyzing the entire gene could also limit our ability to assign the sequences to different species, as reported previously [ 20 ].…”
Section: Discussionmentioning
confidence: 99%